Resiliensi Numerik Calon Guru SD: Urgensi, Tantangan, dan Strategi Mental Menghadapi Transformasi Literasi Abad 21 - Rakhmawati, Yeni; Putri, Agnesi Sekarsari; Syamsi, Ibnu (Paedagogie, 2025)
Numerical resilience plays a role as a way of adapting teachers in various very fast rates of change in the field of numeracy. The scope of numerical resilience is endurance in studying numerical problems. This study aims to provide an overview of the numerical resilience of prospective elementary school teachers. To accommodate this goal, the article is divided into two main sections: What is the urgency of numerical resilience? What needs to be prepared in numerical resilience in elementary school teacher candidates? These two questions are translated into a study that can provide an overview of the role of numeracy resilience and what elementary school teacher candidates need to prepare.